Weathering of field-collected floating and stranded Macondo oils during and shortly after the Deepwater Horizon oil spill. Issue 1 (15th April 2016) - Stout, Scott A.; Payne, James R.; Emsbo-Mattingly, Stephen D.; Baker, Gregory
Abstract: Chemical analysis of large populations of floating (n = 62) and stranded (n = 1174) Macondo oils collected from the northern Gulf of Mexico sea surface and shorelines during or within seven weeks of the end of the Deepwater Horizon oil spill demonstrates the range, rates, and processes affecting surface oil weathering. Oil collected immediately upon reaching the sea surface had already lost most mass below n- C8 from dissolution of soluble aliphatics, monoaromatics, and naphthalenes during the oil's ascent with further reductions extending up to n- C13 due to the onset of evaporation. With additional time, weathering of the floating and stranded oils advanced with total PAH (TPAH50 ) depletions averaging 69 ± 23% for floating oils and 94 ± 3% for stranded oils caused by the combined effects of evaporation, dissolution, and photo-oxidation, the latter of which also reduced triaromatic steroid biomarkers. Biodegradation was not evident among the coalesced floating oils studied, but had commenced in some stranded oils. Graphical abstract: Highlights: Chemical analysis of over 1200 floating and stranded oils reveals weathering. Macondo oil was already weathered upon reaching the sea surface. Evaporation, dissolution and photo-oxidation progressively affected the floating oil. Oils stranded on shorelines were further weathered, including biodegraded.